Composition, antibacterial and antioxidant activities of Pimpinella saxifraga essential oil and application to cheese preservation as coating additive. (1st August 2019) - Ksouda, Ghada; Sellimi, Sabrine; Merlier, Franck; Falcimaigne-cordin, Aude; Thomasset, Brigitte; Nasri, Moncef; Hajji, Mohamed
Highlights: The main compound of Pimpinella saxifraga essential oil (PSEO) was anethole. PSEO showed potential antioxidant and antibacterial activities. The study of acute toxicity of PSEO showed that estimated LD50 was 939 mg/kg. Addition of PSEO in sodium alginate coating improved cheese preservation. Sensory analysis showed consumer appreciation of coated cheese using PSEO. Abstract: The effect of Pimpinella saxifraga essential oil (PSEO) addition (1–3%) in sodium alginate coating on the bacterial and oxidative stability of cheese was studied during refrigerated storage. The GC–HRMS analysis of PSEO showed that anethole, pseudoisoeugenol and p -anisaldehyde were the main components. The PSEO exhibited strong in vitro DPPH radical scavenging activity (IC50 = 6.81 µg/mL), β -carotene bleaching inhibition (IC50 = 206 µg/mL), ferric reducing power (EC50 = 35.20 µg/mL), total antioxidant activity (213.96 ± 11.12 µmol/mL α -tocopherol equivalent) and notable DNA protection potential. Additionally, PSEO displayed potent antibacterial activity against 3 Gram-positive and 3 Gram-negative bacteria (MICs = 0.78–3.12 mg/mL). The acute toxicity of PSEO was determined using mice model (LD50 = 976.2 mg/kg). The enrichment of sodium alginate coating with PSEO, particularly at 3%, improved cheese preservation by reducing the weight loss, preserving the pH and color and enhancing oxidative and bacterial stability without unpleased flavor for consumers.